PELAKSANAAN FUNGSI BADAN USAHA MILIK DESA (BUMDes) REMPAK MAJU JAYA DESA REMPAK KECAMATAN SABAK AUH KABUPATEN SIAK - Sulastri, Maya; Rusli, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Implementation of Functions of the Village Owned Enterprises(BUMDes) Rempak Maju Jaya in Rempak Village, Sabak Auh Subdistrict, SiakRegency.This study aims to investigate implementation and the factors that influencethe function implementation the Village Owned Enterprises (BUMDes) Rempak MajuJaya.This study used qualitative methods with descriptive. Data collection techniquesuses Interviews, Observations, and Literature study. By using key informant and theinformant as a supplementary source of information.The results of this study found thatthe Village Owned Enterprises (BUMDes) Rempak Maju Jaya not optimal in functionalimplementation. It can be seen from not achieving the objectives and functions ofvillage owned enterprises that have been established.Kata Kunci: Pelaksanaan, Fungsi,dan Badan Usaha Milik Desa.